2016
DOI: 10.1007/s10236-016-0928-0
|View full text |Cite
|
Sign up to set email alerts
|

Can the Gulf Stream induce coherent short-term fluctuations in sea level along the US East Coast? A modeling study

Abstract: Much attention has been given in recent years to observations and models that show that variations in the transport of the Atlantic Meridional Overturning Circulation (AMOC) and in the Gulf Stream (GS) can contribute to interannual, decadal, and multi-decadal variations in coastal sea level (CSL) along the US East Coast. However, less is known about the impact of short-term (time scales of days to weeks) fluctuations in the GS and their impact on CSL anomalies. Some observations suggest that these anomalies ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 54 publications
1
42
0
Order By: Relevance
“…The high anticorrelations found between the GS flow and SLR along the MAB coast demonstrated the impact of the GS on the coast (e.g., Figure 10 in Ezer et al, 2013). It is suggested that in addition to the direct GS-coastal sea level relation that results in anticorrelation between the GS strength and sea level rise (Ezer, 2016;, there is another mechanism associated with warming of the Subtropical Gyre that can result in opposing coastal sea level response between the SAB and the MAB. While Vale-Levinson et al suggested that these changes are related to cumulative impacts from NAO and ENSO variations, Domingues et al suggested that warming of the FC causes the increased SLR there, while changes in air pressure and wind contributed to a slowdown of SLR in the MAB.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The high anticorrelations found between the GS flow and SLR along the MAB coast demonstrated the impact of the GS on the coast (e.g., Figure 10 in Ezer et al, 2013). It is suggested that in addition to the direct GS-coastal sea level relation that results in anticorrelation between the GS strength and sea level rise (Ezer, 2016;, there is another mechanism associated with warming of the Subtropical Gyre that can result in opposing coastal sea level response between the SAB and the MAB. While Vale-Levinson et al suggested that these changes are related to cumulative impacts from NAO and ENSO variations, Domingues et al suggested that warming of the FC causes the increased SLR there, while changes in air pressure and wind contributed to a slowdown of SLR in the MAB.…”
Section: Discussionmentioning
confidence: 92%
“…• A recent shift in the location of a hot spot for accelerated sea level rise along the U.S. East Coast was investigated • Changes in the Gulf Stream strength and position around 2010 seemed to explain the regional changes in coastal sea level • Interannual and decadal variations in the Gulf Stream can contribute to temporal and spatial changes in sea level rise rates (Hughes & Meredith, 2006;Huthnance, 1978) and limit transfer of signals between the MAB and the SAB, as demonstrated by numerical simulations (Ezer, 2016(Ezer, , 2017.…”
Section: /2019ef001174mentioning
confidence: 99%
See 1 more Smart Citation
“…This flooding can also be exacerbated by changes in ocean circulation, such as variations in the Gulf Stream, and from natural internal climate variability, all of which affect sea level (Carson et al, 2015;Ezer, 2016;Ezer & Atkinson, 2017). Natural internal climate variability (IC) on annual to decadal timescales includes signals such as seasonal cycles, El Niño Southern Oscillation, and Pacific Decadal Oscillation, among others.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects of papers in this Topical Collection include one on process study of the gravity current (Berntsen et al 2016), three on data assimilations (Margvelashvili et al 2016;Peng et al 2016;Zheng et al 2016), two on basin-scale modeling and observational data analyses (Ezer 2016;Quan et al 2016), two on coastal processes (Liu and Chua 2016;Zhu et al 2016), and two on sediment resuspension and tranport (Qiao et al 2016;Yang et al 2016). Berntsen et al (2016) conducted a high-resolution model experiment using a non-hydrostatic model to simulate plume down a canyon under rotation.…”
mentioning
confidence: 99%